The MAK‐Collection for Occupational Health and Safety 2012
DOI: 10.1002/3527600418.mb744050e0022
|View full text |Cite
|
Sign up to set email alerts
|

Copper and its inorganic compounds [MAK Value Documentation, 2006]

Abstract: Published in the series MAK Value Documentations , Vol. 22 (2006) The article contains sections titled: Toxic Effects and Mode of Action Mechanism of Action Toxicokinetics and Metabolism Effects in Humans Single exposures Repeated exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…The toxicity of CuSO 4 in vivo has been comprehensively investigated in previous studies, and its median lethal dose in mice, 3 days after injection, is 29.5 mg/ kg. 44 Another study reported that intraperitoneal injection of CuSO 4 in single doses of 6.6, 13.2, or 19.9 mg/kg body weight produced no micronucleus induction in male CBA mice. 45 Similar results were reported in another study that investigated the bone marrow of the animals treated with intraperitoneal injection of 6.6 mg/kg CuSO 4 after 24 and 48 hours.…”
Section: Research Implicationsmentioning
confidence: 99%
“…The toxicity of CuSO 4 in vivo has been comprehensively investigated in previous studies, and its median lethal dose in mice, 3 days after injection, is 29.5 mg/ kg. 44 Another study reported that intraperitoneal injection of CuSO 4 in single doses of 6.6, 13.2, or 19.9 mg/kg body weight produced no micronucleus induction in male CBA mice. 45 Similar results were reported in another study that investigated the bone marrow of the animals treated with intraperitoneal injection of 6.6 mg/kg CuSO 4 after 24 and 48 hours.…”
Section: Research Implicationsmentioning
confidence: 99%